(untitled) (Global Journal of Management and Business Research, 2022)
Open-source software has made a breakthrough in the traditional intellectual property theory from the aspects of Copyright, patent right, and trademark right, and it has created a new property rights form in the form of license. Taking blockchain as an example, this paper analyzes bitcoin and Ethereum and their open- source licensing strategies. At the same time, it explores the problems encountered in the property rights of open-source blockchain and three possible solutions to this dilemma: The industry-standard licensing plan, blockchain open-source licensing scheme, and open patent scheme. This research will be significant for expanding and enriching the theoretical and practical analysis of blockchain open source in the field of intellectual property.